Hematocrit Values Predict Carotid Intimal-Media Thickness in Obese Patients With Non-Alcoholic Fatty Liver Disease: A Cross-Sectional Study - Tarantino, Giovanni; Barrea, Luigi; Capone, Domenico; Citro, Vincenzo; Mosca, Teresa; Savastano, Silvia (Frontiers in Endocrinology, 2018)
Background Literature data suggest with some criticism that full-fledged cardio-vascular events (acute or chronic) are likely predicted by blood components, which are reported to be associated with the presence/severity of non-alcoholic fatty liver disease (NAFLD). This study was aimed at determining which marker(s) derived from blood count, such as white blood cells, neutrophils, neutrophil/lymphocyte ratio, platelet count, hemoglobin, mean corpuscular volume, hematocrit values were associated with early-stage or subclinical atherosclerosis, in obese patients of various classes suffering from NAFLD. Methods One hundred consecutive obese patients presenting NAFLD at ultrasound, with low prevalence of co-morbidities and no history or instrumental features of cardiovascular diseases, underwent carotid intima-media thickness (IMT) assessment by doppler ultrasonography. All of them were studied taking into account anthropometric parameters, the metabolic profile and inflammatory markers. Results White blood cells and neutrophil count showed no statistical association with IMT, which was predicted by the amount of visceral adiposity, as appreciated by ultrasonography. After adjusting for visceral adiposity and smoking status, only age and hematocrit contextually predicted early atherosclerosis, evaluated as IMT. Visceral adiposity was a confounding factor in foreseeing IMT. Conclusion Hematocrit values along with the patient’s age could suggest an initial atherosclerosis; the fact that this blood test is inexpensive, widely available, easy to carry out and interpret indeed represents an added value.